Premature ovarian insufficiency: an augmenting disorder in the growing female population - A, Gagana B; G, Priyanka D; P, Sunil Gowda H; Syed , Sagheer Ahmed; M, Rupesh Kumar; M, Surabhi H (International Journal of Indigenous Herbs and Drugs, 2023)
A primary ovarian abnormality such as absent menarche (primary amenorrhea) or early depletion of ovarian follicles/arrested folliculogenesis before the age of 40 is described as premature ovarian insufficiency (secondary amenorrhea). Itsprevalence is 1% and 0.1 % in women under 40 and 30 respectively. Common Symptoms include palpitations, excessive sweating, flushes, anxiety, depression, and fatigue. There could be a variety of causes, including chromosomal abnormalities, autoimmune diseases, infections, idiopathic diseases, iatrogenic diseases, and so on. Diagnosis is usually done based on the level of hormones like estradiol, Follicle Stimulating Harmone, and LuteinizingHarmone. Considering the complications of premature ovarian failure, it is necessary to educate the female population about this disorder. Hence, the Present review focuses on the etiology, symptoms, complications, diagnosis, and treatment of premature ovarian failure.